Low level of the plasma sphingolipid, glucosylceramide, is associated with thrombotic diseases. Issue 1 (23rd June 2017) - Deguchi, Hiroshi; Navarro, Silvia; Payne, Amanda B.; Elias, Darlene J.; Dowling, Nicole F.; Austin, Harland D.; España, Francisco; Medina, Pilar; Hooper, W. Craig; Griffin, John H.
Abstract: Essentials Minor abundance plasma lipids, eg, glucosylceramide, can modulate blood coagulation reactions This lipid was measured in plasmas of 1 myocardial infarction and 2 venous thrombosis populations Low plasma glucosylceramide levels were found in each population compared to matched controls Low plasma glucosylceramide levels are associated with venous and arterial thrombosis Background: One previous pilot study suggested the association of low plasma glucosylceramide (GlcCer) levels with venous thrombosis (VTE) risk. Objective: We aimed to confirm and evaluate the association of low plasma GlcCer levels with VTE and myocardial infarction (MI) occurrence, respectively. Patients and Methods: We evaluated the association of GlcCer in two independent case‐control studies of Caucasian VTE populations (N=210 and 636) and one case‐control study of Caucasian MI patients (N=345). Result: Plasma GlcCer levels in VTE patients were lower compared to controls in two independent VTE populations (5.0 vs 5.8 μg/mL, P =.003 for the Scripps registry, and 5.6 vs 6.0 μg/mL, P =.001 for the Valencia registry, respectively). A low plasma GlcCer level (below tenth percentile of controls) was associated with increased VTE occurrence (odds ratio [OR]=3.7 [95% CI, 1.8‐7.9] for Scripps registry and OR=2.1 [95% CI, 1.3‐3.3] for Valencia registry, respectively). For the MI study, the median GlcCer plasma level was lower in MI patients than in controls (4.3 vs 5.6 μg/mL, P <.001), and a low level of GlcCer (below tenth percentile of control) was associated with higher MI occurrence (OR=7.7, [95% CI, 4.3‐13.8]). Conclusion: Lower concentration of GlcCer was associated with VTE occurrence in 2 independent studies and also with MI occurrence in 1 study.